Analisis Pertumbuhan Ekonomi dan Indikator Komposit IPM Terhadap Jumlah Penduduk Miskin di Provinsi Bali Tahun 2004 – 2013 - Finkayana, I Putu Arya; Urmila Dewi, Made Heny (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 7, Juli 2016 (pp. 729-947), 2016)
Poverty is one of the social problems that occur in various areas, including Bali. One of the causes of poverty is the accessibility issue which is an access / a person's ability to get a good basic needs of food, clothing, education, health and decent living. The purpose of this study was to analyze the effect of economic growth and human development index of the number of poor people in the province of Bali.Penelitian using secondary data from the years 2004 - 2013 and using data collection methods non-participant observation. The analysis technique used is multiple linear regression. Based on the analysis found that economic growth, life expectancy, average - the duration of schooling, literacy rates and per capita spending a significant negative effect on the number of poor people in the province of Bali. To reduce poverty, the government is expected to formulate development policies appropriate to their respective districts / municipalities in Bali Province. The policy may be increasing the opening of employment, entrepreneurship development, improvement of the system of employment, improvement of public facilities (health and education) that are expected to improve the welfare of the underprivileged.
Keywords: the poor; economic growth; life expectancy; average - the duration of schooling; literacy rates; spending per capita